Computational study of urban heat island of Putrajaya, Malaysia. (December 2015) - Morris, Kenobi Isima; Aekbal Salleh, Siti; Chan, Andy; Ooi, Maggie Chel Gee; Abakr, Yousif Abdalla; Oozeer, Muhammad Yaasiin; Duda, Michael
Highlights: WRF coupled with Noah/LSM model was successfully verified in tropical country, Malaysia. The city is heating less compared with other cities around the world. In the case of Putrajaya, the garden city concept has proved effective in partly mitigating the heating norm with cities. LCZ–LCZ heating was discovered within the city. Urban heat sink was also noted during mid-hours of the day. Abstract: The administrative capital of Malaysia, Putrajaya, is one of those cities built on the garden-city concept, however, few studies have been devoted to confirm the validity of the concept. Numerical mesoscale Weather Research and Forecasting (WRF) Model was coupled with Noah land surface model and a single layer urban canopy model (UCM) to investigate the existence and distribution of UHI, and the behaviour of urban canopy layer (2-m) temperature of Putrajaya city. Suitability of the model WRF employed in studying UHI phenomenon in the tropical city of Putrajaya, Malaysia was determined. Precincts in Putrajaya city were classified into local climate zones (LCZs) and the contribution of urban fabrics on the spatial and temporal variations of UHI was also investigated. Results of the model were verified with in situ studies of the area, and observational data from Alam Sekitar Malaysia Sdn Bhd (ASMA). Comparison with ASMA observational and in situ data reveals a satisfactory performance of the model. UHI intensity of Putrajaya exhibits a diurnal profile; increasing during the night to a peak value and then diminishing in the morning with a negligible value during mid-day. During the night hours, the UHII ranges from 1.9 °C to 3.1 °C in some of the precincts (LCZs) considered. Overall, average daily intensity of 0.79 °C heating was noted in Putrajaya for the study duration. The overall effect of urbanized LCZs heating of Putrajaya was normalized by the total amount of area reserved for vegetation.